Diseño de un sistema de gestión de inventarios para el control de materiales e insumos del centro comercial caracol en la ciudad de Quito - Anasicha Parco, Julio Wladimir (2022)
The management of inventories within a company is necessary to ensure both the operational part and the timely availability of stocks of materials and supplies. That is why we will carry out the design of an inventory management system for the control of materials and cleaning supplies of the Caracol Shopping Center in the city of Quito, since due to its long history of service it still manages an old system in the management of their inventories, the purpose of the proposed management system is to upgrade to an inventory management system (hybrid), which allows to determine the planned inventory, safety stock and an adequate planning of material and input requirements (MRP), making it more interactive and easy to use for the warehouse manager. It has been decided to investigate this problem since the lack of an inventory management and control system in the Shopping Center has caused deficiency in the control of inputs and outputs, disorganization in its procedures and faulty planning of requirements.